Mouse IgG2a Antibodies Specific for the Commensal Streptococcus mitis Show Stronger Cross-Reactivity with Streptococcus pneumoniae than IgG1 Antibodies - Sudhanshu Shekhar; Rabia Khan; Ata Ul Razzaq Khan; Fernanda Cristina Petersen (Journal of Immunology Research)
Here we show that mouse IgG2a and IgG1 antibodies specific for the commensal Streptococcus mitis cross-react with pathogen Streptococcus pneumoniae serotypes 2 and 4, although the cross-reactivity conferred by IgG2a is stronger than that by IgG1 antibodies. These findings may be important for understanding the S. mitis-induced IgG isotype responses and have consequences for the development of an effective pneumococcal vaccine.